Distance-based cooperative relative localization for leader-following control of MAVs - Nguyen, Thien-Minh (2020)
In multi-robot systems, the capability of each robot to relatively localize its neighbors is a crucial requirement, which needs to be resolved as a prerequisite for almost any distributed scheme of operation. Notably, this problem proves to be quite challenging in GPS-denied environments. In this letter, we investigate a problem of simultaneous relative localization and leader-following control of aerial robots by using only ranging and odometry sensors, waiving the need of external positioning systems. To tackle this challenge, we propose a cooperative estimation-control scheme where specialized agents called orbiters are tasked with maintaining persistently exciting trajectories to facilitate exponential convergence of both relative localization and tracking errors for itself and others. Numerical simulations and experiments on quadcopters in a GPS-denied environment are carried out to validate the theoretical findings.